Strategies Used to Increase Intrinsic Motivation of Colledge Students - Najat Muhammed Amin (Zanco Journal of Humanity Sciences)
Students who are intrinsically motivated are more eager to learn and to develop their capacities through having active participation. According to Self-Determination Theory , fulfilling the psychological needs of students helps students to be intrinsically motivated and to succeed in achieving their academic goals. The aim of this research is to measure the intrinsic motivation of  college students’ and to assess the fulfillment of their psychological needs of autonomy, competence and relatedness which are reinforced mostly by their instructors . It also aims at detecting college instructors' awareness of the satisfactions of the psychological needs of students and to which extent do they try to fulfill such needs. The participants are (40) second year students of English Department - College of Basic Education at Salahaddin University . The data was collected through the use of  TWO questionnaires which are adapted from Goldman et al (2017) ;  the first questionnaire is about the measurement of students' Intrinsic Motivation in Learning Scale (IMLS) of the literature course , while the second one aims at detecting the fulfillment of the Students' Psychological Needs Scale (SPNS)  in the module of Literature which is taught at second stage. The results  showed a positive correlation between the students' perceptions about the fulfillment of their psychological needs with the effective mean of (3.41) and the Students' Level of Intrinsic Motivation with High mean scale of (3.54).The findings showed hopefulness of the instructors awareness of their students psychological needs which increases the level of the students intrinsic motivation.